The plagiatus species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae), and additional data on some species from Japan - Shavrin, Alexey V. (Zootaxa, 2022)
The plagiatus group of the genus Geodromicus Redtenbacher, 1857 includes eight Palaearctic species: the widespread G. plagiatus (Fabricius, 1798), the European G. corsicus Fagel, 1958, G. nigrita (P.W.J. Müller, 1821), G. pedemontanus Fagel, 1958, and G. suturalis (Lacordaire, 1835), and the East Palaearctic G. magnus Shavrin, 2020, G. paramerus Shavrin 2000, and G. shii Cheng & Peng, 2020 (in Cheng et al. 2020). The species group is reviewed, defined, and briefly discussed. The species are illustrated and a key is provided. Two additional species groups are established for four species from Japan with a strongly sclerotized flagellum: the aokii group, containing G. aokii (Watanabe, 1972) and G. sprius (Watanabe, 1990), and the sinuatus group containing G. sinuatus (Sharp, 1889) and G. suensoni Bernhauer, 1936. Both groups are defined, briefly discussed, and a key to each group is given. Several new synonymies are established: G. plagiatus = G. (s.str.) klimai A. Bordoni, 1984 syn. n., = G. (s.str.) schoenmanni A. Bordoni, 1984 syn. n.; G. nigrita = G. nigrita lohsei Jarrige, 1963 syn. n., = G. niveus Bernhauer, 1941 syn. n.; G. sinuatus = G. watanabei Hayashi, 2018 syn. n.; G. suensoni = G. takabai Hayashi, 2018 syn. n. Lectotypes of Staphylinus plagiatus Fabricius, 1798 and Anthophagus sinuatus Sharp, 1889 are designated. Distribution maps are provided for G. plagiatus, G. sinuatus, and G. suensoni. Geodromicus plagiatus is recorded from Cataluña province of Spain, Moldova, Georgia, Uzbekistan, and several regions of Russia (Pskov Area, Stavropol Area, Karachay-Cherkess and Chechen republics, Sverdlovsk Area, Khanty-Mansi Autonomous Region, Krasnoyarsk Territory, Evenkia and Yakutia), G. nigrita from Andorra and G. suturalis from Slovenia for the first time.